2021
DOI: 10.1017/s0714980821000477
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and Social Connectedness Across the Adult Lifespan in the Context of the COVID-19 Pandemic

Abstract: The coronavirus disease (COVID-19) pandemic has had profound consequences on collective mental health and well-being, and yet, older adults appear better off than younger adults. The current study examined mental health impacts of the pandemic across adult age groups in a large sample (n = 5,320) of Canadians using multiple hierarchical regression analyses. Results suggest older adults are experiencing better mental health and more social connectedness relative to younger adults. Loneliness predicted negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 58 publications
(122 reference statements)
2
5
1
Order By: Relevance
“…A national survey from Cigna reported that all ages may experience social isolation and loneliness [7]. The findings also corresponded to the prior literature showing high loneliness and/isolation and stress among older adults [3,29], as well as among young adults [8,9] during COVID-19. In addition, our study found that the Bigs experienced slightly higher levels of loneliness than the Minis.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…A national survey from Cigna reported that all ages may experience social isolation and loneliness [7]. The findings also corresponded to the prior literature showing high loneliness and/isolation and stress among older adults [3,29], as well as among young adults [8,9] during COVID-19. In addition, our study found that the Bigs experienced slightly higher levels of loneliness than the Minis.…”
Section: Discussionsupporting
confidence: 81%
“…For example, Generation Z (age [18][19][20][21][22] has been reported as the loneliest generation [7]. COVID-19 also significantly increased young adults' loneliness or decreased their social connectedness [8,9], which negatively influenced their mental health [10]. One study found that loneliness, rather than financial worries or concerns about the health impacts of COVID-19, was the single most important driver of reported emotional or mental health difficulties among young adults [11].…”
Section: Introductionmentioning
confidence: 99%
“…Our sample was less older adult and predominantly middle-aged, which may explain why there was no significant change in subjective social connectedness in our study. Our findings are consistent with previous studies in that age and educational attainment are strongly correlated with depression symptoms ( 62 , 63 ), and age is also associated with anxiety symptoms ( 63 ). We found that anxiety and depression scores before quarantine negatively predicted changes in anxiety and depression scores from quarantine measures, possibly because people with more anxiety and depression symptoms before isolation would show a decrease in anxiety and depression during quarantine ( 64 ).…”
Section: Discussionsupporting
confidence: 93%
“…Although this investigation was not designed to test the consequences of social distancing, this was a time when social interactions were salient. For example, a study using one large Canadian sample reported that loneliness experienced amidst the pandemic was associated with anxiety and depression in all age groups (Gregory et al, 2021), although adults 55 years of age and older were the least likely to report worsening mental health symptoms. Loneliness, depression symptoms, and dampened well-being resulting from lockdowns were also often a function of the extent to which people lost access to social relationships (e.g., Birditt, Turkelson, Fingerman, Polenick, & Oya, 2021;Krendl & Perry, 2021).…”
Section: The Current Studymentioning
confidence: 99%